ANTECEDENTS AND CONSEQUENCES EFFECT OF PATIENT SATISFACTION IN XYZ HOSPITAL - Satyawati Satyawati; Margaretha Pink Berlianto (Universitas Pelita Harapan, 2022)
Purpose – This research aims to analyze the antecedents and consequences effect of patient satisfaction on patient loyalty in XYZ hospital BogorDesign/Methodology/Approach –This study used quantitative research and data collection was collected using questionnaire. The target population of this research were in patient at XYZ hospital and willing to be respondents of this research. The number of samples were determined to be which 212 samples. The sampling technique use was purposive sampling. Partial Least Square-Structural Equation modelling (PLS-SEM) is applied to this study.Findings – The result of data analysis showed that quality of object, quality of infrastructure, quality of interaction, dan quality of atmosphere have positive effect on patient satisfaction, Quality of process has a negative effect on patient satisfaction. Lastly patient satisfaction have positive effect on patient loyaltyResearch Limitations/Implications – This research only focuses on hospitalized patient, limitation time and only at one hospital. The focus on this research to analyze the effect of 5Q service quality : quality of object, quality of process, quality of infrastructure, quality of interaction, quality of atmosphere on patient satisfaction, and patient satisfaction on patient loyaltyPratical Implication – The result of data analysis, XYZ hospital can improve quality of object, quality of infrastructure, quality of interaction, quality of atmosphere and redesign the quality of process to increase patient satisfaction and patient loyaltyOriginality/Value – This research gives information to XYZ hospital management to make improvement and further planning how to increase service quality effort to increase the patient satisfaction and the patient loyalty